The Effectiveness of Cognitive Behavioral Therapy Group Counseling to Improve the Resilience of Students as Divorce Victims - Setyorini, Wiji Wahyu; Eddy Wibowo, Mungin; Awalya, Awalya (Universitas Negeri Semarang, 2021)
Studies focusing on the provision of intervention for students as divorce victims are truly limited, so the present study aimed to prove that CBT group counseling with cognitive restructuring technique is effective to improve the resilience of students as divorce victims. Here the researchers used multiple pretest posttest design by involving students as divorce victims in SMP Negeri Juwana, Pati Regency, Central Java. Their data were collected using resilience scale. Based on the results of repeated measure test, the CBT group counseling with cognitive restructuring technique was effective to improve the resilience of students as divorce victims by having F(1, 8)=275.03,p<0.001). Another proof was showed by the results of within subject test showing the resilience improvement by the cognitive restructuring technique from pretest (M=57.62, SD=2.29), posttest (M=82.87, SD=1.34), and follow-up (M=86.50, SD=0.98). This study confirms the effectiveness of CBT group counseling with cognitive restructuring technique to improve the resilience of students as victims of divorce.